DEPENDENCE MODEL OF FREIGHT TURNOVER IN ROAD TRANSPORT ON THE PRICE OF A-95 GASOLINE - Maiborodina, N. V.; Gerasymenko, V. P. (Systems and Technologies, 2025)
Road transport ranks second in Ukraine among modes of transport in terms of freight volume. This is why there is a need to study, model, analyze, and forecast freight traffic in road transport. The behavior and value of any economic indicator depend on a multitude of factors, but it is impossible to take all of them into account. However, this is not necessary. Typically, only a limited number of factors significantly influence the indicator under study. The impact of other factors is so negligible that ignoring them does not lead to substantial deviations in the behavior of the object under analysis. A key prerequisite for a quality analysis and forecast is identifying and considering only the dominant factors in the model. One of the most important factors influencing road freight traffic is the price of fuel. This paper examines the issue of modeling road freight traffic depending on the price of A-95 gasoline. To construct the mathematical model, statistical data from the State Statistics Service of Ukraine was used. To automate the process of building the model of the dependence of freight volume on road transport on the price of A-95 gasoline, this study employed the capabilities of the Excel spreadsheet processor. To ensure the reliability of the constructed model, the regression line option with the highest approximation value was selected among those offered in Excel. This work adheres to all the requirements for the main stages of mathematical modeling of a real-world process: the problem is stated, the key influencing indicator is identified, the methodology for constructing the mathematical model is presented, the developed model of the real process is analyzed, and the application of the obtained results for the practical task of forecasting road freight traffic for the year 2025 is considered. The results obtained in this study play an important role in planning the volume of goods transported by road and in analyzing the volume of external and internal trade in goods.